2018
DOI: 10.1039/c7cp06742a
|View full text |Cite
|
Sign up to set email alerts
|

XANES study of vanadium and nitrogen dopants in photocatalytic TiO2 thin films

Abstract: We report an X-ray absorption near edge structure (XANES) study of vanadium (V) and nitrogen (N) dopants in anatase TiO thin films deposited by radio-frequency magnetron sputtering. Measurements at the Ti K and V K edges were combined with soft X-ray experiments at the Ti L, O K and N K edges. Full potential ab initio spectral simulations of the V, O and N K-edges were carried out for different possible configurations of substitutional and interstitial dopant-related point defects in the anatase structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…A previous electrochemical study showed that -NO2 reduction takes place at about 0.5 eV below the CBM [52]. Since sub-bandgap visible light cannot promote electronic transitions from the valence to the conduction band, the initial electron state must be an intra-gap state associated with V, which is incorporated as a substitutional V 4+ cation in the lattice of both rutile and anatase [43,44]. There is a significant spread in the calculated energy level of the electronic state localized on V 4+ , which was reported between 0.7 eV [16,20] and 1.36 eV [21] below the CBM.…”
Section: Correlation Between Charge Carrier Dynamics and Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…A previous electrochemical study showed that -NO2 reduction takes place at about 0.5 eV below the CBM [52]. Since sub-bandgap visible light cannot promote electronic transitions from the valence to the conduction band, the initial electron state must be an intra-gap state associated with V, which is incorporated as a substitutional V 4+ cation in the lattice of both rutile and anatase [43,44]. There is a significant spread in the calculated energy level of the electronic state localized on V 4+ , which was reported between 0.7 eV [16,20] and 1.36 eV [21] below the CBM.…”
Section: Correlation Between Charge Carrier Dynamics and Photocatalysismentioning
confidence: 99%
“…Studies of the local structure of V dopants in TiO2 provide the essential prerequisite for an understanding of the optical properties and of the charge carrier dynamics. We have recently published X-ray Absorption Fine Structure (XAFS) studies which demonstrate that V always occupies a substitutional site in V-TiO2 NPs [43] and in V-TiO2 thin films [44] irrespective of whether they have mainly anatase or rutile structure. By exploiting the chemical sensitivity of XAFS, we have also performed a differential illumination High Energy Resolution Fluorescence Detected (HERFD) -X-ray Absorption Near Edge Structure (XANES) experiment on V-TiO2 NPs [45].…”
Section: Introductionmentioning
confidence: 99%
“…According to molecular orbital theory, the O K-edge features originate from a transition of the O 1s electron to the various partially occupied and unoccupied molecular orbitals of the oxides, considering the crystal-field splitting effects [ 31 ]. As shown in the O K-edge XANES spectrum of the pristine K 2 Ti 8 O 17 sample, the major peaks located at about 532.6 eV and 534.1 eV are assigned to excitations varying from the O 1s core level to the Ti 3d-related conduction band, splitting into t 2g and e g subbands [ 32 ]. This result confirms the partial reduction of Ti 4+ during the discharge of the K 2 Ti 8 O 17 electrode.…”
Section: Resultsmentioning
confidence: 99%
“…This limitation can be overcome by doping or inclusion of metallic nanoparticles. By using XAS, including ab -initio full potential simulations, we have shown that V dopants in TiO2 nanoparticles and thin films occupy substitutional sites, irrespective of whether the oxide matrix has a rutile, anatase or mixed structure; N dopants, instead, are found both in substitutional anionic sites and as N2 dimers [1,2]. These structural studies are complemented with a quantification of materials functionality, correlated to the charge carrier dynamics studied by ultra fast optical spectroscopy [3].…”
mentioning
confidence: 95%